Analisis Value Chain Guna Mencapai Strategi Cost Leadership dalam Meningkatkan Efesiensi Biaya (Studi pada Perusahaan X di Sidoarjo) - Heri Widodo (BISMA (Bisnis dan Manajemen), 2018)
This research aim for knowing, how value chain analysis was do in company value chain for achieve cost leadership strategy in increasing cost efficiency. According to value chain analysis explained what activities made company value chain, therefore will be know value addedd activity and non value added activity. In the same way, research in value chain analysis can showing company activity. This activity can devided into primary activity and supporting activity, value added activity and non value added activity and cost trigger, therefore cost efficiency can be achieve which reducing and eliminate wate activity. In conclusion, this research can be a input for company, while taking corporate strategy to increase profit and give value added for costumer. Value chain analysis will achieve cost leadership can increase company competitive adventage because it can increase cost efficiency.